Bibliometric Mapping of WhatsApp-Based Health Research (2015–2025): Global Trends, Leading Countries, and Emerging Themes - Intan Gumilang Pratiwi; E.W.N Sofianto; Baiq Yuni Fitri Hamidiyanti; Ati Sulianty; Margareta Melani; Qorinah Estiningtyas Sakilah Adnani (Media Kesehatan Politeknik Kesehatan Makassar, 2025)
The use of WhatsApp (WA) in the health sector is increasingly widespread for communication, education, and intervention. Yet, systematic and updated bibliometric analyses of global trends remain limited, particularly those covering post-2023 developments and comparing contributions between high-income and developing countries. This study aims to systematically map and analyze the international landscape of WA-based health research published between 2015 and 2025. We employed a bibliometric research design with data sourced from the Scopus database, using the keywords "WhatsApp" AND "health". A total of 50 relevant articles were analyzed using descriptive statistics and VOSviewer software to visualize networks. The findings indicate that the use of WA as a health communication tool is firmly established. Publication trends indicate growth, with the COVID-19 pandemic serving as a significant catalyst that has driven the exploration of WA for remote healthcare services. The five most productive countries are India, Saudi Arabia (with five articles each), Brazil, Malaysia, and Indonesia (with four articles each). The most influential themes centered on the benefits of WA in clinical practice and the enhancement of supervision for community health workers. In conclusion, WA is proven to be a vital health communication tool, and the future direction of research is expected to increasingly focus on establishing its effectiveness, testing service models, and its broader, more systematic integration into the digital health ecosystem.